1999
DOI: 10.1002/(sici)1098-2396(199904)32:1<23::aid-syn3>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Opioid peptide receptor studies, 11: Involvement of Tyr148, Trp318 and His319 of the rat ?-opioid receptor in binding of ?-selective ligands

Abstract: Previous data obtained with the cloned rat µ opioid receptor demonstrated that the ''super-potent'' opiates, ohmefentanyl (RTI-4614-4) and its four enantiomers, differ in binding affinity, potency, efficacy, and intrinsic efficacy. Molecular modeling (Tang et al., 1996) of fentanyl derivatives binding to the µ receptor suggests that Asp147, Tyr148, Trp318, and His319 are important residues for binding. According to this model, Asp147 interacts with the positively charged opiate agonist to form potent electrost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
41
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 19 publications
7
41
0
Order By: Relevance
“…24 , 72 For example, the ␦ -selective ligand 1 shows enhanced activity for the receptor when a phenethyl moiety replaces the propyl-containing lead. 72 Additionally, it has been shown that N-phenethylmorphine shows greater potency than its parent compound morphine. 73 Also important to note is that this pocket contains several residues that can hydrogen-bond with the hydroxyl group of ohmefentanyl, specifi cally a threonine in TM II.…”
Section: Fentanyl and Analogsmentioning
confidence: 61%
See 4 more Smart Citations
“…24 , 72 For example, the ␦ -selective ligand 1 shows enhanced activity for the receptor when a phenethyl moiety replaces the propyl-containing lead. 72 Additionally, it has been shown that N-phenethylmorphine shows greater potency than its parent compound morphine. 73 Also important to note is that this pocket contains several residues that can hydrogen-bond with the hydroxyl group of ohmefentanyl, specifi cally a threonine in TM II.…”
Section: Fentanyl and Analogsmentioning
confidence: 61%
“…In fact, confl icting pharmacophores have been proposed for each ligand class. [24][25][26][27][28][29][30] For the ␦ -selective SNC 80 derivatives, controversy exists over whether the pharmacophoric determinants of SNC 80 (and analogs) are the same as those for the ␦ -selective opiates NTI and SIOM. [57][58][59] For the fentanyls and arylacetamides, different yet important discrepancies exist.…”
Section: Selective Nonopiate Ligandsmentioning
confidence: 99%
See 3 more Smart Citations